The Role of Teachers and Parents in The Formation of Children's Character in Schools: A Study in Southeast Sulawesi, Islamic Family Law Perspective - Aminudin, Aminudin; Hasan, Hasan (El-Usrah: Jurnal Hukum Keluarga, 2025)
Globalization poses a significant threat to the moral values of younger generations, making cultivating akhlakul karimah (noble character) among students an urgent priority. The synergy between character education conducted by teachers at school and by parents at home is deemed crucial to ensure the consistent internalization of Islamic values in children. This study aims to analyze the role of teacher–parent collaboration in shaping akhlakul karimah among students at Al-Wahdah Integrated Islamic Elementary School in Bombana, Southeast Sulawesi from the perspective of Islamic Family Law. A qualitative research method with a case study approach was employed, involving in-depth interviews with teachers, parents, and school administrators, participatory observation of the learning environment, and document analysis of school policies and Islamic family law literature. Data were analyzed descriptively and thematically to identify collaborative patterns in character education. The findings indicate that the moral quality of students is strongly influenced by family-based nurturing, underscoring the importance of teacher-parent collaboration to tailor character-building efforts to each student’s unique needs. This partnership effectively comprehensively reinforces students’ moral development—encompassing spiritual, social, and environmental dimensions—resulting in positive behavioral changes. From the perspective of Islamic Family Law, this synergy represents a shared responsibility between parents as primary educators and teachers as formal educators to foster a generation with noble character. These results align with Islamic educational theory, which posits that effective moral education requires the harmonious involvement of the family, school, and broader community